Online environment for data acquisition from car sensors (Automatyka/Automatics, 2019)
Modern cars are equipped with a lot of  electronic devices called Electronic Control Units (ECU). They collect diagnostic data from different car components to control their work, assess the quality of their work and and detect defects. Regardless of the development of on-board computers in cars, only a small amount of information is passed on to the driver. The paper describes how to build a data collecting environment for acquisition real data from a car. The system whose components include an Android based smartphone and Torque PRO application is able to send data via the Internet in real-time to the chosen server. The collected data can be further analysed both on-line and off-line.